Chronic exposure of bisphenol S (BPS) affect hypothalamic-pituitary-testicular activities in adult male rats: possible in estrogenic mode of action - Hizb Ullah; Faizan Ullah; Owais Rehman; Sarwat Jahan; Tayyaba Afsar; Dara Al-Disi; Ali Almajwal; Suhail Razak (Komiyama Printing Co. Ltd, 2021)
Abstract Background The industrial revolution has resulted in increased synthesis and the introduction of a variety of compounds into the environment and their potentially hazardous effects have been observed in the biota. The present study was aimed to evaluate the potential endocrine-disrupting effects of chronic exposure to the low concentrations of bisphenol S (BPS) in male rats. Methods Weaning male Sprague-Dawley rats (22 days old) were either exposed to water containing 0.1% ethanol for control or different concentrations of BPS (0.5, 5, and 50 μg/L) in drinking water for 48 weeks in the chronic exposure study. After completion of the experimental period, animals were dissected and different parameters (hormone concentrations, histology of testis and epididymis, oxidative stress and level of antioxidant enzymes in the testis, daily sperm production (DSP), and sperm parameters) were determined. Results Results of the present study showed a significant alteration in the gonadosomatic index (GSI) and relative reproductive organ weights. Oxidative stress in the testis was significantly elevated while sperm motility, daily sperm production, and the number of sperm in epididymis were reduced. Plasma testosterone, luteinizing hormone (LH), and follicle-stimulating hormone (FSH) concentrations were reduced and estradiol levels were high in the 50 μg/L-exposed group. Histological observations involved a significant reduction in the epithelial height of the testis along with disrupted spermatogenesis, an empty lumen of the seminiferous tubules, and the caput region of the epididymis. Conclusion These results suggest that exposure to 5 and 50 μg/L of BPS for the chronic duration started from an early age can induce structural changes in testicular tissue architecture and endocrine alterations in the male reproductive system which may lead to infertility in males.